Effects of two-dimensional cyber incivility on employee well-being from a self-determination perspective - Xiao, Shuai-Ping; Lu, Yi; Yan, Yu; Zhou, Zhiqing E.; Cao, Zhao-Xue; Zhao, Kai-Chen (Frontiers in Psychology, 2023)
With the increased use of remote working, people are paying more attention to cyber incivility. Although many scholars have studied cyber incivility, its mechanisms affecting employee well-being remain to be explored due to the lack of focus and in-depth discussion of its two dimensions. Based on self-determination theory and regulatory focus theory, this research examined the mediating role of intrinsic motivation and the moderating role of promotion focus between cyber incivility and employee well-being through two studies. The results of Study 1 demonstrated that both active and passive cyber incivility predicted increased emotional exhaustion, and intrinsic motivation was an important mediator. High promotion focus aggravated the negative effect of passive cyber incivility on intrinsic motivation but did not moderate the relationship with active cyber incivility. Study 2’s results were similar as above, except that promotion focus did not moderate the effect of passive cyber incivility. As a result, the literature on the mechanisms of workplace mistreatment has been enriched by this research, which also helps to design intervention strategies to lessen or avoid the harmful effects of work-related stressful events on employee well-being.